2014
DOI: 10.1007/s00264-014-2441-8
|View full text |Cite
|
Sign up to set email alerts
|

Radial tunnel syndrome: results of surgical decompression by a postero-lateral approach

Abstract: Purpose Our purpose is to describe the results obtained in surgical treatment of a series of patients with symptoms of radial tunnel syndrome. Methods We performed a prospective study on 42 patients (43 limbs) operated for radial tunnel syndrome between 1996 and 2010, using a posterior-external approach. Results Using the Roles and Maudsley criteria, 21 patients had excellent results (48.8%), 16 good (37.2%) and six fair results (13.9%). Most patients were satisfied with the surgery, reporting symptom relief a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Quantitative data were present in some studies, 10 , 11 , 14 , 15 , 17 , 18 and utilized the self-reported DASH/QuickDash and Roles & Maudsley tools. In general, the majority of studies described the open technique with muscle release associated with external neurolysis in the radial nerve.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative data were present in some studies, 10 , 11 , 14 , 15 , 17 , 18 and utilized the self-reported DASH/QuickDash and Roles & Maudsley tools. In general, the majority of studies described the open technique with muscle release associated with external neurolysis in the radial nerve.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, several studies have reported results from surgical decompression in small cohorts of patients with additional techniques for decompression, including a straight dorsolateral incision (Figure 2A) with dissection between the extensor carpi radialis longus and ECRB along with fat transfer above the decompressed PIN to prevent scar formation. [34][35][36][37][38] Others have decompressed the nerve at the interval between the BR and wrist extensors (Figure 2B). A summary of surgical approaches to PIN release is presented in Table 2.…”
Section: Surgical Release and Outcomesmentioning
confidence: 99%
“…[28] Stanley ve arkadaşlarına ettiklerini ve bu cerrahi tedavinin başarısının yüksek olduğunu bildirmişlerdir. [30] PİN tuzaklanmasındaki ikinci klinik tabloda, el-bilek ve parmak ekstansiyonunda kademeli veya ani güç kaybı görülür. Temelde, radyal sinirin tünel içerisinde tuzaklanması RTS olarak isimlendirilirken, tünel sonrası PİN basısı posterior interosseöz sendromu olarak adlandırılır.…”
Section: Posteri̇or İnterosseöz Si̇ni̇ri̇n (Pi̇n) Tuzaklanmasiunclassified